Innovative technology for the production of road surfacing through the melting of natural rock materials (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The paper advances an author’s concept of an in-situ monolithic pavement produced by thermal melting of natural rock followed by controlled cooling. A process flow is outlined (subgrade preparation—high-temperature heating—melt leveling—gradient cooling), along with rock-selection criteria and pre-project testing. Engineering constraints, HS&E aspects, and a pilot validation program for mountainous regions are discussed.
Keywords: rock thermofusion; monolithic pavement; glass-ceramics; basalt; mountainous regions; Kyrgyzstan